FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - MUNGNIYATI MUNGNIYATI; MARSELLA UTOMO (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to determine and examine audit committe, size of board, the independent proportion of the board of commissioners, leverage, firm size and profitability in affecting firm value in manufacture companies listed in Indonesia Stock Exchange. This research uses data from 102 manufacture companies listed on the Indonesia stock exchange (IDX) from the period 2014 to 2016. Data for this study were selected using purposive sampling method. The data in the model were analyzed using multiple linear regressions analysis method to determine the model of research. The result of this research indicate that audit committe, the independent proportion of the board of commissioners, leverage, and profitability had influence towards firm value whereas size of board and firm size had no influence towards firm value.